PLACENTA PREVIA: CLINICAL COURSE, DIAGNOSIS AND DELIVERY TACTICS - Hamraeva Madina (The Conference Hub, 2025)
Placenta previa remains one of the most dangerous pregnancy pathologies, associated with a high risk of antenatal and intrapartum bleeding, anemia, and perinatal complications. The increasing incidence of this pathology is associated with the increasing number of uterine surgeries, primarily cesarean sections. The aim of this study was to investigate the clinical features of pregnancy with placenta previa, evaluate the diagnostic capabilities of ultrasound methods, and develop optimal labor management strategies.
Keywords: placenta previa, pregnancy, cesarean section, bleeding, diagnosis, labor management strategies.